1980
DOI: 10.1146/annurev.ph.42.030180.000525
|View full text |Cite
|
Sign up to set email alerts
|

Binding and Metabolism of Sex Steroids by the Hypothalamic-Pituitary Unit: Physiological Implications

Abstract: INTRODUCTION +1256During the past decade, putative receptor systems for sex steroid hormones have been identifi ed, characterized, and anatomically mapped in the brains and pituitary glands of representative vertebrate species. This information has been obtained by three techniques: (a) steroid autoradiography after in vivo 3H-steroid administration (36,68), and (b) in vitro receptor assays as well as (c) in vivo 3H-steroid administration and cell nuclear isolation, both performed on dissected pieces of brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0
2

Year Published

1982
1982
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 34 publications
3
23
0
2
Order By: Relevance
“…Connolly, Roselli, and Resko (1990) have demonstrated that adult male guinea pig brains contained higher quantities of androgen aromatase than female brains. Androgen aromatase is concentrated in the limbic system and hypothalamus (amygdala, preoptic area, septum, hippocampus, and medial basal hypothalamus), whereas low levels were consistently found in cortical tissue (McEwen, 1980). Furthermore, female rats treated with T show a more marked enhancement of social aggression than rats treated with the nonaromatizable androgen dihydrotestosterone (DHT).…”
Section: Androgen Metabolismmentioning
confidence: 99%
“…Connolly, Roselli, and Resko (1990) have demonstrated that adult male guinea pig brains contained higher quantities of androgen aromatase than female brains. Androgen aromatase is concentrated in the limbic system and hypothalamus (amygdala, preoptic area, septum, hippocampus, and medial basal hypothalamus), whereas low levels were consistently found in cortical tissue (McEwen, 1980). Furthermore, female rats treated with T show a more marked enhancement of social aggression than rats treated with the nonaromatizable androgen dihydrotestosterone (DHT).…”
Section: Androgen Metabolismmentioning
confidence: 99%
“…In the adult rat testosterone could modulate the phasic release of somatostatin (14) and it is an essential component in the expression of the male GH secretory pattern Recently we found that the GH-releasing and hypotensive action of clonidine were lost in long-term castrated rats. These effects have been restored by testosterone replacement of the castrates (1 6).…”
mentioning
confidence: 93%
“…Ainsi le nucleus des r6gions pr6 optiques est plus volumineux chez les rats males [7] et la portion moyenne du noyau de l'amygdale m6diane est 6galement plus 61ev4e [20]. Le ganglion sympathique cervical sup4rieur est plus grand [18]. La testost6rone est capable d'augmenter le facteur de croissance nerveuse [3] conduisant ~ une augmentation de la survie neuronale [10].…”
Section: Resumeunclassified
“…La testost6rone est capable d'augmenter le facteur de croissance nerveuse [3] conduisant ~ une augmentation de la survie neuronale [10]. Ces actions paraissent s'expliquer par une concentration 41ev6e de r6cepteurs aux androg6nes dans l'hypophyse, l'hypothalamus, la r6gion pr4optique, le septum et l'amygdale [18].…”
Section: Resumeunclassified